Pengembangan Media Pembelajaran Interaktif Berbasis PMRI Menggunakan Macromedia Flash Profesional 8 - Iwan Suryadi; Yufitri Yanto; Novianti Mandasari (Jurnal Pendidikan Matematika:Judika Education, 2020)
This study aims to develop PMRI-based interactive learning media using professional macromedia flash 8 on square and rectangular subject matter for grade VII students of SMP Negeri 8 lubuklinggau, as well as knowing the quality of mathematics learning media developed from aspects of validity and practicality. The research method used is the Research & Development method based on the ADDIE development model. The ADDIE development model consists of 5 stages: analysis (Analyze); planning (design); development (Development); implementation (Implementation) and (5) evaluation (Evaluation). The results of this study produce a valid and practical interactive learning media. The results of validation by material experts and media experts indicate that PMRI-based interactive learning media using professional macromedia flash 8 square and rectangular subject matter meet very valid criteria with an average score of 4.22. As for the practicality assessment that was tested by teachers and students found to meet very practical criteria with an average score of 4.45. In conclusion, the development of interactive learning media using PMRI based using Macromedia Flash Professional 8 on the subject matter of square and rectangular for VII grade students of SMP Negeri 8 lubuklinggau shows valid and practical criteria to use. Keywords: Interactive learning media, Macromedia Flash, PMRI, Square and Rectangle.